The Influence of Digital Transformation Based on Religious Ethics on MSME Performance in the Industry 4.0 Era - Shofiyuddin, Muhammad; Nurhayati, Siti; Marlinah Manggor, Enny; Zahro (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The rapid advancement of Industry 4.0 necessitates that Micro, Small, and Medium Enterprises (MSMEs) adopt digital transformation to enhance competitiveness and long-term sustainability. However, in regions where religious values significantly shape business practices, digital transformation must align with ethical considerations. This study examines the impact of digital transformation, moderated by religious ethics, on MSME performance in Pekalongan City, Central Java, Indonesia. Employing a quantitative approach with a census method, the research surveyed 180 MSMEs that have integrated digital technologies while adhering to religious ethical principles. Data analysis was conducted using Structural Equation Modeling - Partial Least Squares (SEM-PLS) with WarpPLS 8.0 software. The findings indicate that digital transformation significantly enhances MSME performance, with religious ethics playing a crucial role in reinforcing ethical decision-making and ensuring business sustainability. Additionally, religious ethics moderate the relationship between digital transformation and business performance, fostering trust, accountability, and social responsibility. This study underscores the need for policy interventions, improved digital literacy, and enhanced infrastructure to facilitate MSME digitalization. By bridging the gap between digital transformation and ethical business practices, the research contributes to the disclosurse on sustainable MSME development within Islamic economic frameworks.